UPAYA SEKOLAH DALAM PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) DI BENGKEL PEMESINAN SMK NEGERI 2 MUARA ENIM: School Efforts In Implementing Occupational Safety And Health (Osh) In The Machine Shop Of Smk Negeri 2 Muara Enim - Adytia Agustri; Nopriyanti (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
This research aims to determine how schools implement Occupational Safety and Health (OSH) in the machining workshop of SMK Negeri 2 Muara Enim. This research is a naturalistic study, with data collection techniques using in-depth interviews. The data sources for this research employed snowball sampling techniques, starting with the head of the machining workshop and the machining teachers. Data analysis in this study used the Miles, Huberman & Saldana data analysis model with the assistance of Nvivo 12 Pro software. The results of this study indicate that SMK Negeri 2 Muara Enim shows serious efforts in implementing Occupational Safety and Health (OSH), particularly in the machining workshop through OSH training, OSH culture, routine maintenance, and the provision of adequate facilities.